Too easy to keep : life-sentenced prisoners and the future of mass incarceration - Herbert, Steven Kelly, 1959- (University of California Press, 2019)
"'Some guys don't break any rules. They do their jobs, they go to school, they don't commit any infractions, they keep their cells clean and tidy, and they follow the rules. And usually those are our LWOPs [life without parole]. They're usually our easiest keepers.' Too Easy to Keep provides directs much-needed attention toward a neglected group of American prisoners--the large and growing population of those inmates serving life sentences. Relying heavily on extensive interviews with lifers and with prison staff, Too Easy to Keep charts the challenges that a life sentence poses--both to the prisoners and to the staffers charged with caring for them. Surprisingly, many lifers show remarkable resilience and craft lives of notable purpose. Yet their eventual decline will pose challenges for the institutions that house them. Rich in data, Too Easy to Keep illustrates the harsh consequences of excessive sentences and demonstrates a keen need to reconsider punishment policy"--Provided by publisher.